2019
DOI: 10.1111/sms.13591
|View full text |Cite
|
Sign up to set email alerts
|

No association between perceived exertion and session duration with hamstring injury occurrence in professional football

Abstract: Training and competition loads have emerged as modifiable composite risk factors of non‐contact injury. Hamstring strains are the most common injuries in football with substantial burden on the individual player and club. Nevertheless, robust evidence of a consistent load‐hamstring injury relationship in professional football is lacking. Using available data from the Qatar Stars League over three competitive seasons, this study investigated the separate and combined effects of perceived exertion and session du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Other statistical variances that require attention in this body of research moving forward include appropriate sample-size calculations for the number of predictors that researchers intend to use in their models. 44 Using pseudo-R 2 statistics, Lolli et al, 45 in their 2019 paper on perceived exertion, session duration, and hamstrings injury, determined that sample sizes of 329, 583, or 1166 players were needed for 1, 5, or 10 load-related predictors, respectively. None of the studies in this review came close to those sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Other statistical variances that require attention in this body of research moving forward include appropriate sample-size calculations for the number of predictors that researchers intend to use in their models. 44 Using pseudo-R 2 statistics, Lolli et al, 45 in their 2019 paper on perceived exertion, session duration, and hamstrings injury, determined that sample sizes of 329, 583, or 1166 players were needed for 1, 5, or 10 load-related predictors, respectively. None of the studies in this review came close to those sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined the association between external/internal training load and injury in professional soccer players, with highly inconsistent findings ranging from significant interrelationships to clear disassociations (Hulin et al, 2016;Bowen et al, 2017Bowen et al, , 2020Malone et al, 2017;Fanchini et al, 2018;Lolli et al, 2019). Using the external load to describe the relationships between ACWR and injury risk, Hulin et al (2016) found that the ratio of acute to chronic workloads (absolute total distance) predicted injuries in elite rugby players.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the aforementioned findings, recent articles using internal load indicators suggest a poor interrelationship between the ACWR and injury incidence (Fanchini et al, 2018;Lolli et al, 2019). In professional soccer players, increased ACWRs were associated with poor predictive validity in identifying players who will suffer a future injury (Fanchini et al, 2018), and the relationships between match and training loads with hamstring injuries showed no associations between ACWRs and injury occurrence in professional football (Lolli et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations